DIAGNOSTIC ACCURACY OF ULTRASONOGRAPHY IN ACUTE APPENDICITIS - Hussain, Sajjad; Rahman, Asif; Abbasi, Tariq; Aziz, Tariq (Journal of Ayub Medical College Abbottabad, 2014)
Background: The diagnosis of acute appendicitis is mainly clinical and to augment the clinical diagnosis ultrasonography and Computerized Tomographic Scan of the abdomen are also being used to help in diagnosis of the disease; which all carry some inherent limitations. This study was done to establish diagnostic accuracy of Ultrasonography (USG) in acute appendicitis taking histopathology of removed appendix as the gold standard. Methods: This cross-sectional validation study was conducted in Radiology Department, Military Hospital and Combined Military Hospital Rawalpindi from July 2007 to January 2008. Sixty cases of clinically suspected acute appendicitis were selected on non-probability convenience sampling technique. All of them underwent ultrasound evaluation. Diagnostic accuracy of USG was calculated keeping histopathology of the removed appendix as gold standard whenever appendectomy was carried out. Results: Out of 60 patients whose USG of right lower quadrant was performed, 30 patients were correctly diagnosed as having acute appendicitis on USG out of 34 finally diagnosed cases based on histopathology. Similarly we picked 12 normal appendices out of 26 non-appendicitis patients. This showed that US scan has sensitivity of 88%, specificity of 92%, positive predictive value of 94%, negative predictive value of 86%, and overall accuracy of 90%. The most accurate appendiceal finding for appendicitis was a diameter of 7 mm or larger followed by non-compressibility of inflamed appendix. Conclusion: Ultrasonography has high accuracy in diagnosing acute appendicitis and reduces negative appendectomies. Greater than 6-mm diameter of the appendix under compression is the most accurate USG finding with high positive predictive value for the diagnosis of acute appendicitis. Keywords: Ultrasonography, Appendix, Appendicitis, Appendectomy